50 pies, 50 states : an immigrant's love letter to the United States through pie - Fong, Stacey Mei Yan (Voracious, Little, Brown and Company, 2023)
"An Asian immigrant and home baker presents a love letter to her adopted country with recipes for pies from every state such as Mississippi Mud Pie and Kentucky Derby Pie"--